Cover Image, Volume 114, Number 8, August 2017. Issue 8 (26th June 2017) - Droz, Xuan; Harraghy, Niamh; Lançon, Etienne; Le Fourn, Valérie; Calabrese, David; Colombet, Thierry; Liechti, Pascal; Rida, Amar; Girod, Pierre‐Alain; Mermod, Nicolas
Abstract : Cover Legend The cover image, by Xuan Droz et al., is based on the Article Automated microfluidic sorting of mammalian cells labeled with magnetic microparticles for those that efficiently express and secrete a protein of interest, DOI:10.1002/bit.26270 .